Fibre Characteristics of Paper and Paper Egg Tray Used In Southwestern Nigeria (2016)
Fibre characteristics of paper and paper egg tray (locally manufactured and imported brands) used in Southwestern Nigeria was investigated. 14 different brands of paper and paperboard were selected to cover the available varieties of paper and paperboard for egg tray production. Paper samples were obtained from identified paper egg tray producing establishments, printing press and other sources in the region. A total of 9 paper egg tray brands of local and imported categories were also obtained for characterization based on users’ recommendation. 25mm by 25mm of each test specimen was put in test tube containing warm water of 50ºc, for 24 hours. Representative samples of separated fibres in the suspension were mounted on slides and measured under a Ritchert Light Microscope x80 magnification. Twenty (20) representative fibres were selected and measured in order to keep error below 5% for a 95% confidence level. Results obtained showed that sample papers and boards were made of heterogeneous fibrous materials; and their fibre quality compromised. Local paper egg trays were made of comparatively lower fibre quality.